Fatores condicionantes dos movimentos de massa no município de Agudo/RS - Behling, Angéli Aline (2017)
In the municipality of Agudo, located in the central region of Rio Grande do Sul, several scars of mass movements have been identified mainly in its rural area, reaching fields and vicinal roads, damaging the flow of agricultural production. This research has as main objective to identify the conditioning factors of the mass movements in the municipality of Agudo, seeking to contribute with information that can help the Public Power in the management of this type of socio environmental process. To achieve the proposed goal were located the scars of mass movements that already occurred. The classification and evaluation of each process in the field were performed based on the inspection report, modified from Technical Standard ABNT-11682 (2009). Eleven processes were identified, whose locations were plotted on thematic maps, related to the conditioning factors, considered important for this study, such as: hypsometry, slope shape, slope, geology, soils and use and occupation. It was identified: fall, wedge slip, creeps, rotational landslides, landslides, and landslides with debris flow, the last two being the most significant. The result of this research indicates that the factors that condition the most significant processes that are planar landslides and debris flow are: hypsometry above 159 meters and slope greater than 27% can reached up to 89%. The scar ruptures is predominantly found in colluvial contact with residual soil (Typic) or altered sedimentary rock. The scars are located in predominantly concave slopes - converged, especially in the case of debris flow, indicating concentration of surface and underground water flow. These processes occurred in areas of arboreal vegetation, with little or no anthropogenic interference. The methodology used to evaluate the processes in the field was effective, allowing to qualify the information obtained from the thematic maps, whose scales of information were more regional.